A Study on the Satire and Humor Techniques in Iranian Folklore Legends - Fatemeh Noofeli; Zarin taj Varedi (نثرپژوهی ادب فارسی, 2019)
Satire and humor are forms of lyric literature that have always drawn attention from official authors and poets. As satire in valuation of official art tries to follow serious objective in the form of laughter and mockery and its horizons and territories in social affairs are quite wide, its role is also considerable in the folklore and especially in folk legends. Satire in the legends, similar to other texts, is a form of criticism of life issues and is a serious speech in the form of humor, which can criticize all political, economic, cultural and social arenas. By a content analysis approach of qualitative and induction type, this study tries to analyze satire and humor methods from Iranian Legends and Fairy Tales Encyclopedia by ‘Ali Ashraf Darvishiyan and Reza Khandan. Among the objectives of this research is to show satire methods in two fields of content and language. Based on the research results, satire techniques in folk legends include stupidity, obscurity, inconsistency and incompatibility of components and position, personification, humorous name, humorous title and other techniques. Among the various applications of satire in the folklore legends could be referred to entertainment, criticism, correction and promotion of ethical and educational values. Many of the mentioned techniques in folklore legends include sexual and taboo issues, since, unlike official culture, the folklore culture contains lesser censorship and also, releasing internal tensions is one of the applications of folklore satire.